Vitamin D and behavioral disorders in older adults: results from the CLIP study - Lucie Gilbert; Alexis Bourgeais; Spyridon N Karras; Duygu Gezen-Ak; Erdinç Dursun; Cédric Annweiler (Elsevier, 2024)
Objectives: Vitamin D is involved in brain health and function. Our objective was to determine whether vitamin D deficiency was associated with behavioral disorders in geriatric patients. Design: The observational cross-sectional CLIP (Cognition and LIPophilic vitamins) study. The report followed the STROBE statement. Setting: Geriatric acute care unit in a tertiary university hospital in France for 3 months at the end of winter and beginning of spring. Participants: 272 patients ≥65 years consecutively hospitalized or seen in consultation. Measurements: Participants were separated into two groups according to vitamin D deficiency (i.e., serum 25-hydroxyvitamin D ≤25 nmol/L). Behavior was assessed using the reduced version of the Neuropsychiatric Inventory Scale (NPI-R) score and subscores. Age, sex, BMI, education level, comorbidities, MMSE and GDS scores, use psychoactive drugs and vitamin D supplements, and serum concentrations of calcium, parathyroid hormone, TSH and estimated glomerular filtration rate (eGFR) were used as potential confounders. Results: Participants with vitamin D deficiency (n = 78) had similar NPI-R score (17.4 ± 20.3 versus 17.2 ± 16.1, p = 0.92) but higher (i.e., worse) subscore of agitation and aggressiveness (2.0 ± 3.3 versus 1.2 ± 2.4, p = 0.02) and higher (i.e., worse) subscore of disinhibition (0.99 ± 2.98 versus 0.38 ± 1.42, p = 0.02) than those without vitamin D deficiency (n = 194). In multiple linear regressions, vitamin D deficiency was inversely associated with the subscore of agitation and aggressiveness (β = 1.37, p = 0.005) and with the subscore of disinhibition (β = 0.96, p = 0.008). Conclusion: Vitamin D deficiency was associated with more severe subscores of agitation and aggressiveness and of disinhibition among older adults. This provides a scientific basis to test the efficacy of vitamin D supplementation on behavioral disorders in older patients with vitamin D deficiency.